Descoberta de novos antivirais para Flavivírus a partir de uma abordagem fenotípica - Pilger, Denise Regina Bairros De [UNIFESP] (2019)
The Flavivirus genus comprises more than 70 pathogenic viruses with different pathologies and a significant public health impact in different regions of the world, with potential to emerge in non-endemic regions. Dengue virus (DENV), yellow fever (YFV) and Zika (ZIKV) are some of the most important human pathogenic flaviviruses with similar symptoms ranging from mild fever and malaise to hemorrhage, shock and failure of multiple organs. Despite the existence of protective vaccines for both viruses, their use is contraindicated for immunocompromised individuals, pregnant women and children. The only treatment is the mitigation of symptoms associated with diseases, with analgesics, antipyretics and replacement of body fluid. Specific antiviral chemotherapies could reduce the morbidity and mortality associated with these infections. In addition, during an outbreak, a specific drug could be administered at the onset of any symptoms associated with infections. Therefore, there is an urgent need to establish a more objective, sensitive and reproducible biological assay to search new antiviral therapies. Thus, an image-based phenotypic assay was developed and optimized for the screening of three commercial compound libraries (NIH Clinical Collection, National Institute of Health, LOPAC1280, Sigma, and Pathogen Box, MMV) against a panel of viruses of the genus Flavivirus. We highlight the results obtained through: (i) NIH library, from which we identified two compounds against dengue virus serotype 2 with high selectivity (> 10); (ii) LOPAC1280, from which we identified three compounds with promising activity against the yellow fever virus. In addition, the activity spectrum of these compounds was evaluated against other viruses of the same genus, as well as their ability to induce resistance in yellow fever virus, and how they interact with the viral life cycle. (iii) Pathogen Box library was screened in parallel with six different viruses to stablish an activity profile of the compounds. As a result, 133 compounds were selected, some of which have already been described as having antiviral activity, validating the assay as a viable tool for the discovery of candidates with potential antiviral activity. In summary, the methodology described in this work represents an important contribution to the initial processes of antiviral development. With these experiments it was possible to find new potent and effective compounds for YFV, which provides a solid contribution to the early stages of the discovery of new drugs for diseases caused by flavivirus.